Behavioral indices of moderate nigrostriatal 6–hydroxydopamine lesion: a preclinical Parkinson's model. - Fornaguera Trías, Jaime (1993)
Asymmetries in turning and scanning were investigated in rats with different degrees of neostriatal dopamine depletion after unilateral injections of 6-hydroxydopamine into the substantia nigra. Animals with severe lesions, i. e., residual dopamine levels of <20%, spontaneously turned ipsiversive and showed more scanning behavior with the side ipsilateral to the lesion. These asymmetries were reversed by the dopamine receptor agonist apomorphine. Animals with less severe dopamine depletion, i. e., residual dopamine levels of 20–65%, did not show an asymmetry in spontaneous turning, but an ipsilateral asymmetry in scanning was still observed, indicating a greater sensitivity of this measure for moderate striatal dopamine depletions. Furthermore, in animals with residual dopamine levels of 45–65%, the dopamine receptor agonist apomorphine did not lead to a behavioral reversal as with severe lesions, but induced ipsilateral scanning and ipsiversive turning. These ipsiversive asymmetries are discussed in relation to asymmetries in self-regulatory mechanisms of the nigro-striatal dopamine system, such as dopamine autoreceptors controlling the release of this transmitter. Dopamine receptor-stimulated behavioral asymmetry in animals with moderate depletions of dopamine is suggested as a preclinical model to study mechanisms affected in the early state of Parkinson's disease.